Modeling Inherently Homogeneous Sintering Processes. Issue 5 (19th April 2018) - Raether, Friedrich; Seifert, Gerhard
Abstract: A novel Monte Carlo model for the simulation of sintering processes is introduced. Different from previous models, local interface curvature is considered in the acceptance of diffusion steps. This enables the investigation of the effects of interface energies on the sintering process. Sintering paths are calculated for various microstructures and interface energies. Results are interpreted in the framework of thermodynamic criteria for homogeneous sintering processes which were presented recently. Abstract : During sinter processes, thermodynamic driving forces may cause inhomogeneity in the emerging microstructure . A Monte Carlo algorithm is developed and applied to the case of solid phase sintering with the goal of identifying inherently homogeneous sintering conditions. Simulations based on representative volume elements suggest that large dihedral angles, fast surface diffusion, and low grain growth during the final densification phase are a favorable situation for achieving homogeneous microstructures through sinter processing.